1992
DOI: 10.1021/jm00099a010
|View full text |Cite
|
Sign up to set email alerts
|

4-Substituted thiophene- and furan-2-sulfonamides as topical carbonic anhydrase inhibitors

Abstract: A series of 4-substituted thiophene- and furan-2-sulfonamides was prepared and was found to possess nanomolar-level potency for inhibition of human carbonic anhydrase II in vitro. Selected examples from this group were further evaluated for their potential to act as topically effective ocular hypotensive agents in the ocular normotensive albino rabbit and the ocular alpha-chymotrypsinized rabbit. Solubility studies in water and pH 7.4 buffer were carried out to estimate the ability of compounds to be formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The aspect of increased potency is nicely illustrated by Mannich adducts 57 and 58 that were synthesized from corresponding 4-hydroxybenzoyl and 4-hydroxybenzenesulfonyl thiophene-2-sulfonamides by Hartman et al 39 (Scheme 21). Compounds 57 and 58 (as well as their furan analogs) demonstrated inhibitory activity against hCA II and their IC 50 values were found to be in the nanomolar range.…”
Section: Mannich Reaction In Synthesis Of Caismentioning
confidence: 97%
“…The aspect of increased potency is nicely illustrated by Mannich adducts 57 and 58 that were synthesized from corresponding 4-hydroxybenzoyl and 4-hydroxybenzenesulfonyl thiophene-2-sulfonamides by Hartman et al 39 (Scheme 21). Compounds 57 and 58 (as well as their furan analogs) demonstrated inhibitory activity against hCA II and their IC 50 values were found to be in the nanomolar range.…”
Section: Mannich Reaction In Synthesis Of Caismentioning
confidence: 97%
“…Hartman et al 34 synthesized a series of 4-substituted thiophene and was found to possess nanomolar-level potency for inhibition of hCA II in vitro. Selected compounds from this group were further evaluated for their potential to act as topically effective ocular hypotensive agents in the ocular normotensive albino rabbit and the ocular α-chymotrypsinized rabbit.…”
Section: Thiophenementioning
confidence: 99%
“…It might be intriguing to investigate whether electron-withdrawing groups at C3 will allow desulfonylation in related structures. The electrophilicity of sulfonamides, attached to various heterocycles, has been assessed by measuring their rate of reaction with GSH (Graham et al, , 1990Woltersdorf et al, 1989;Hartman et al, 1992). Sulfonamides attached to benzothiazole were more reactive with GSH compared with those attached to benzofuran, benzoxazole, or indole.…”
Section: Desulfonylation Of a Sulfonylfuropyridinementioning
confidence: 99%